Enhancing Students’ Motivation in Learning English Through Wordwall at SMPN 2 Pitu Riase - Nova Azis; Sam Hermansyah; Nur Hikmah; Nurul Faradillah (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
The reason to choose this title because it was found that many students had low motivation to learn English. Most of them considered English difficult to understand and irrelevant to their daily communication. This study aimed to explore how the use of Wordwall enhances students’ motivation in learning English and to examine students’ responses toward its implementation in the classroom at SMP Negeri 2 Pitu Riase. The study focused on identifying changes in students’ motivation, participation, and engagement before and after the use of Wordwall as a learning medium. This research employed a descriptive qualitative approach. The data were collected through open-ended interviews (pre-intervention and post-intervention), classroom observations, and documentation. The participants consisted of 10 seventh-grade students selected through purposive sampling. The data were analyzed using an interactive qualitative analysis model including data reduction, data display, and conclusion drawing. The findings showed that the use of Wordwall significantly enhanced students’ motivation in learning English. Before the implementation, students tended to feel bored, less interested, and passive during the learning process. After using Wordwall, students became more enthusiastic, active, and confident in participating in classroom activities. In addition, students responded positively to the use of Wordwall as it created a more interactive, enjoyable, and engaging learning environment. Overall, Wordwall proved to be an effective digital learning medium to improve students’ motivation and participation in English learning.